Evaluating farmers' satisfaction from high-yielding rice (Oryza sativa) variety cultivation in boro season: evidence from adaptive trials in Bangladesh - Hassan, Md. Masudul; Habib, Muhammad Ashraful; Nayak, Swati; Jewel, Zilhas Ahmed; Resmi, Samira Islam; Hasan, Mahamudul (Springer, 2025)
Farmer satisfaction with high-yielding rice varieties (HYVs) in head-to-head adaptive trials (HHATs) was carried out over different agroecological zones (AEZs) during the boro season in Bangladesh. Despite the agronomic viability of high-yielding rice varieties (HYVs), there is a paucity of empirical data about the influence of institutional coordination and agronomic support on farmer satisfaction during the adaptation process. This study seeks to address this gap through a mixed-methods methodology. Using a structured questionnaire, primary data was collected from 280 farmers. A purposive sampling method was employed for a cross-sectional study. The study used descriptive statistics, reliability analysis, exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and structural equation modeling (SEM) to estimate variables and identify causal relationships. The EFA identified four leading factors influencing satisfaction: agro-technical support, institutional support and coordination, input quality and seed performance, and farmers' satisfaction and implementation success. CFA validated institutional oversight (IO) and agro-technical efficiency (ATE), which retained for SEM analysis. Overall, farmers' satisfaction is effectively anticipated by SEM, exposing satisfactory fit indices (CFI = 0.917, RMSEA = 0.091, GFI = 0.99) with both factors ATE (β = 0.684, p < 0.001) and IO (β = 0.259, p < 0.05). NVivo (v14.0)-based qualitative analysis revealed by highlighting primary impediments like labor shortages, irrigation challenges, and climate risk for successful HHATs implementation. This research supports Sustainable Development Goals (SDGs) 2 (Zero Hunger), 13 (Climate Action), and 17 (Partnerships for the Goals) through the promotion of climate-resilient and inclusive agricultural transformation. This study employs participatory innovation approaches through HHATs to offer evidence-based recommendations to enhance acceptance and satisfaction with HYVs in different areas of Bangladesh. These findings reinforce ongoing policy discussions around sustainable rice intensification in South Asia.